2021
DOI: 10.3389/fmolb.2021.645831
|View full text |Cite
|
Sign up to set email alerts
|

WDR45 Mutation Impairs the Autophagic Degradation of Transferrin Receptor and Promotes Ferroptosis

Abstract: WDR45 is an autophagy-related protein that involves in the formation of autophagosome. Mutations in WDR45 lead to the impairment of autophagy which is associated with the human β-propeller protein-associated neurodegeneration (BPAN). However, the relationship between autophagy and brain iron accumulation in patients with BPAN remains unclear. Here, we demonstrated that transferrin receptor (TfRC) which is critical for the iron import of cells was degraded via autophagy. TfRC was accumulated after the inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…This phenotype suggests that the inability of cells to obtain the iron stored in ferritin generates a deregulated iron uptake, possibly as a compensatory response. Another mechanism that could contribute to iron accumulation is the deficiency in the autophagic degradation of TfR1, also observed in WDR45-mutant cells [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…This phenotype suggests that the inability of cells to obtain the iron stored in ferritin generates a deregulated iron uptake, possibly as a compensatory response. Another mechanism that could contribute to iron accumulation is the deficiency in the autophagic degradation of TfR1, also observed in WDR45-mutant cells [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Xiong et al reported that WDR45-deficient cells showed transferrin receptor accumulation, which affects autophagic degradation. They also suggested that WDR45 mutation could promote ferroptosis by lipid peroxidation and ROS production [ 16 ]. ROS from iron metabolism can induce ferroptosis; it is also correlated with NADPH oxidase activity and lipid peroxidation products.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired ferritinophagy and non-transferrin-bound iron pathway were confirmed to mediate the accumulation of iron in another cellular BPAN model [234] whereby iron was detected mostly in lysosomal vesicles [235]. Yet another study employing the cellular BPAN model found accumulation of TfR in cells overexpressing mutated WDR45 that was associated with increased Fe levels [236]. Interestingly, increased ratio between serum concentration of soluble TfR and logarithm of serum ferritin concentration (sTfR/logFerrit) was observed in five BPAN patients, suggesting complex systemic disruption of Fe metabolism [86].…”
Section: Neurodegenerations With Brain Iron Accumulation (Nbia) Groupmentioning
confidence: 90%